Advances in bioconversion of organic solid wastes for the preparation of high-value medium-chain fatty acids - HE Zilin; REN Weitong; WU Qinglian; GUO Wanqian* (能源环境保护)
With increasing industrialization and urbanization, organic solid wastes production is rising. Resource utilization of these wastes has become an emerging area of research in ecological and environmental protection. Among various approaches, utilizing organic solid waste as a fermentation substrate for microbial carbon chain elongation technology to produce valuable medium-chain fatty acids (MCFAs) is gaining significant interest. This technology not only addresses pressing environmental pollution problems but also enhances product value, offering both environmental protection and economic benefits. It aligns perfectly with China′s policies on pollution reduction, carbon mitigation, and the development of waste-free cities. The review focuses on the reaction mechanisms and key microorganisms involved in the anaerobic fermentation and carbon chain elongation technologies for the bioconversion of organic solid wastes to prepare MCFAs. The main factors affecting the synthesis efficiency, including pH, temperature, substrate type and concentration, hydraulic retention time (HRT), solid retentiontime (SRT), and other factors are analyzed. Furthermore, the challenges associated with the production of MCFAs from organic solid wastes, such as the limited bioavailability of the substrate, the lack of electron donors, the complexity of constructing a high-efficiency acid-producing system, and the issues related to product separation and extraction, are summarized. Finally, this review provides suggestions for future research and development in related fields.